PERLINDUNGAN HAK-HAK KREDITUR DALAM HAL ADANYA PENGALIHAN BENDA JAMINAN OLEH PIHAK DEBITUR - Mahendra, Lidya; Murni, R.A. Retno; Sumertayasa, Putu Gede Arya (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 2 (2016)DO - 10.24843/AC.2016.v01.i02.p13, 2016)
The development of era requires people to move forward. One of them is the progress in the field of business that requires additional funding from the Bank. Extension of credit by the Bank generally will be accompanied by additional collateral in the form of movable or immovable objects. Collateral with moving objects is referred to as fiduciary collateral. Article 23 paragraph (2) of the Fiduciary Law No. 42 of 1999 states that the Giver of Fiduciary may not assign, pledge, or lease to another party objects into objects that do not constitute Fiduciary inventory objects, except with the prior written consent of the Beneficiary of Fiduciary . In fact, there are debtors who transfer their objects of collateral that resulted in losses to the Bank. Based on the gap between the das Sein and the das Solen, then it can be formulated problems of how the protection of the rights of creditors in the case of the transfer of collateral objects by the debtors to a third party and what legal actions can be taken by the creditors in the event of the objects of fiduciary collateral are transferred to any third parties by the debtors at the time of execution of the fiduciary security object.
Keywords: Protection of Creditor' s Rights, Fiduciary, Transfer of the Collateral Objects.